The impact of gross domestic product, trade openness, air transportation, and total final energy on carbon dioxide emission in Malaysia - Adwina Chin Lee Ling; Saizal Pinjaman; Sarma Aralas (Penerbit Universiti Malaysia Sabah, 2025)
The current paper provides an empirical analysis of the relationship between carbon dioxide (CO2) emissions and economic factors, namely Gross Domestic Product (GDP), air transportation, energy consumption, and trade openness in Malaysia, based on the annual data from 1990 until 2016. By utilizing the cointegration analysis, it is demonstrated that CO2 emissions exhibit a positive and significant long-run relationship with air transportation and energy consumption. Meanwhile, GDP and trade openness are significant in influencing CO2 emissions in the short run. It was also demonstrated that the disturbances fluctuate while entering the long-run relationship in a dampening manner rather than monotonically. It is advised for policymakers to continually consider the movements of these economic determinants due to their significant effect on CO2 emissions in Malaysia in both the short and long run.